Laboratory diagnostics for HIV infection - Stefano Buttò; Barbara Suligoi; Emanuele Fanales-Belasio; Mariangela Raimondo (Istituto Superiore di Sanità, 2010)
Laboratory diagnosis of human immunodeficiency virus (HIV) infection is fundamental for detecting and monitoring infection. Many diagnostic tools are available that are based on both detection of HIV-specific antibodies and virus antigen, or nucleic acid. As technology evolves, HIV testing assays are being improved providing better sensitivity and specificity. In this short review, we summarize the common and new methodologies that are being used in laboratories, from the HIV antibody-based assays to the new tests for the detection of HIV nucleic acids.